The interplay between academic performance, emotional intelligence, and self-concept as predictors of violent behavior in higher education: a multi-group structural equation modeling - Ubago-Jiménez, José Luis; Corral-Robles, Silvia; Ortega-Martín, José Luis; Melguizo-Ibáñez, Eduardo (Frontiers in Psychology, 2023)
Higher education is a focus of increasing violent behavior. The evidence suggests an obsession to achieve the best academic performance in order to access working life. This research aims to develop an explanatory model of violent behavior and its relationship with self-concept and emotional intelligence according to in relation to their academic performance. A sample of 932 Spanish undergraduate students participated in the multi-group structural equation modeling. Findings revealed that students who have a higher academic performance have problems to control and regulate their emotions, showing signs of direct and indirect violence. Moreover, it was found that that emotional intelligence and self-concept have a direct influence on episodes of violent behavior, with academic performance being a key component affecting each variable. The present study provides some implications and suggests some avenues for future research.